MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS APLIKASI DAN TEKNOLOGI INFORMASI - Desnita Armi; Sandriansyah; Alvia Ramadhani; Nurfaizah; Yuda Aditama; Ami Latifah (UNISAN JURNAL, 2023)
This exploration means to depict Islamic strict training learning media in light of utilizations and data innovation. The composing technique utilizes writing studies obtained from library writing or library materials, either as books or articles distributed in printed or online logical diaries. The information got is checked on/broke down and afterward introduced unmistakably as articles. In light of the exploration that has been completed, the creator can reason that: Learning media, as a device in the growing experience, has a few advantages, including 1) Educating draws in more consideration of students so it can cultivate learning inspiration; 2) The importance of showing materials will be more clear, so they can be seen so understudies can figure out them, and will empower understudies to dominate the showing targets well; 3) Learning techniques fluctuate, not just verbal correspondence through the educator’s expressed words, understudies don’t get exhausted, and instructors don’t run out of energy. In basic terms, data innovation can be supposed to be the science expected to oversee data with the goal that the data can be looked effectively and precisely. The substance of this information can be as methods and techniques for putting away data proficiently and really.